KINERJA BANK SYARIAH : PENGUNGKAPAN ICSR BERDASARKAN TEORI STAKEHOLDER DARI PERSPEKTIF ISLAM - Leonita Suryani; Rita Wijayanti (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of Islamic Corporate Social Responsibility disclosure on the performance of Islamic banks in an Islamic perspective which provides benefits for companies to provide ideas about applying the variables in this study so as to improve the performance of Islamic banks in the future. The population and this research are Islamic commercial banks registered with the Financial Services Authority (OJK) with a sample of 12 banks from 2012-2020. ICSR disclosures are prepared using AAOIFI standards which have 8 indicators and 78 disclosures, while bank performance is measured by Return On Assets (ROA) and Return On Equity (ROE). Of the 8 indicators in this study, ethical behavior, management, sharia compliance, research, development and training have an effect on bank performance, while products and services, environment, employees, and social activities have no effect on Islamic bank performance.